(untitled) (The International Journal for Scientific Research, 2023)
Introduction: Total knee replacement (TKR) surgery is a common procedure for severe knee osteoarthritis, improving the quality of life for many patients. Despite surgical success, optimal recovery heavily relies on effective post-operative rehabilitation. This systematic review aimed to evaluate the effectiveness of various physiotherapy exercises in enhancing recovery outcomes following TKR, focusing on knee function, pain reduction, and patient satisfaction. Methods: A comprehensive search of PubMed, Scopus, Cochrane Library, and Web of Science was conducted, focusing on interventional studies and clinical trials published in the last five years up to 2022. Studies included were those evaluating physiotherapy interventions post-TKR, with clear measures on efficacy regarding patient outcomes. Exclusion criteria encompassed non-exercise-based rehabilitations, observational studies, and non-English publications. Data extraction focused on intervention types, sample sizes, and outcome measures. Results: Twelve studies were included, with sample sizes ranging from 30 to over 200 participants. Interventions varied from in-person physiotherapy, home-based exercises, high-intensity training, to tele-rehabilitation. High-intensity physiotherapy programs were associated with a 40% greater improvement in knee function compared to standard care. Tele-rehabilitation provided comparable outcomes in terms of pain management and mobility improvements, with patient satisfaction exceeding 80% in some studies. However, adherence and exercise intensity were noted challenges in remote settings. Conclusions: The review highlights physiotherapy’s pivotal role in post-TKR recovery, with high-intensity programs showing significant benefits in knee function. Tele-rehabilitation emerges as a promising alternative, potentially increasing access to care. These findings support the integration of structured physiotherapy into rehabilitation protocols to maximize recovery outcomes. Future research should explore strategies to enhance adherence and effectiveness of tele-rehabilitation services.